واقع تبني الحكومة الإلكترونية في الدول العربية: استعراض لمؤشرات التطبيق مع الإشارة لحالة الجزائر - خنوش، صليحة (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2020)
Tills study aims to shed light on some of the leading Arab experiences in the field of application of e-government in order to draw lessons and benefit from them. As well as presenting the reality of the application of e-government in Algeria, through reviewing e-government indicators of the countries studied. Tills study shows that e-government in Algeria has not lived up to the required level because of its occupation of late ranks in the e-government development index. Algeria is ranked 150th globally with an average of 0.4227 capacity indicator which is an average value, and also the Electronic Participation Index never exceeds 0.2022 and it is a weak value in the ranking of 165 worldwide in 2018. this delay is due to a number of obstacles which hinder the successful implementation of e-government project in Algeria.
Keywords: الحكومة الإلكترونية -- الجزائر -- الدول العربية -- الخدمات الإلكترونية